Identification of a 53kDa protein, as a new high molecular weight allergen from fraxinusexcelsior (Ash) pollen - Shoushtari, Maryam Sharif; Majd, Ahmad; Assarehzadegan, Mohammad-Ali; Fanuel, Songwe; Moin, Mostafa; Nejadsattari, Taher; Shoormasti, Raheleh Shokouhi; Badalzadeh, Mohsen; Tajik, Shaghayegh; Fazlollahi, Mohammad Reza; Tayebi, Behnoosh; Pourpak, Zahra; et al. (Springer Medizin, 2021)
Background Fraxinus excelsior (Ash) is a common tree and is important cause of winter–spring pollinosis in many temperate regions in the world. In this study, a high molecular weight allergen from ash pollen was identified.